Prevention of preeclampsia with aspirin - Rolnik, Daniel L.; Nicolaides, Kypros H.; Poon, Liona C. (American journal of obstetrics and gynecology, 2022)
Preeclampsia is defined as hypertension arising after 20 weeks of gestational age with proteinuria or other signs of end-organ damage and is an important cause of maternal and perinatal morbidity and mortality, particularly when of early onset. Although a significant amount of research has been dedicated in identifying preventive measures for preeclampsia, the incidence of the condition has been relatively unchanged in the last decades. This could be attributed to the fact that the underlying pathophysiology of preeclampsia is not entirely understood. There is increasing evidence suggesting that suboptimal trophoblastic invasion leads to an imbalance of angiogenic and antiangiogenic proteins, ultimately causing widespread inflammation and endothelial damage, increased platelet aggregation, and thrombotic events with placental infarcts. Aspirin at doses below 300 mg selectively and irreversibly inactivates the cyclooxygenase-1 enzyme, suppressing the production of prostaglandins and thromboxane and inhibiting inflammation and platelet aggregation. Such an effect has led to the hypothesis that aspirin could be useful for preventing preeclampsia. The first possible link between the use of aspirin and the prevention of preeclampsia was suggested by a case report published in 1978, followed by the first randomized controlled trial published in 1985. Since then, numerous randomized trials have been published, reporting the safety of the use of aspirin in pregnancy and the inconsistent effects of aspirin on the rates of preeclampsia. These inconsistencies, however, can be largely explained by a high degree of heterogeneity regarding the selection of trial participants, baseline risk of the included women, dosage of aspirin, gestational age of prophylaxis initiation, and preeclampsia definition. An individual patient data meta-analysis has indicated a modest 10% reduction in preeclampsia rates with the use of aspirin, but later meta-analyses of aggregate data have revealed a dose-response effect of aspirin on preeclampsia rates, which is maximized when the medication is initiated before 16 weeks of gestational age. Recently, the Aspirin for Evidence-Based Preeclampsia Prevention trial has revealed that aspirin at a daily dosage of 150 mg, initiated before 16 weeks of gestational age, and given at night to a high-risk population, identified by a combined first trimester screening test, reduces the incidence of preterm preeclampsia by 62%. A secondary analysis of the Aspirin for Evidence-Based Preeclampsia Prevention trial data also indicated a reduction in the length of stay in the neonatal intensive care unit by 68% compared with placebo, mainly because of a reduction in births before 32 weeks of gestational age with preeclampsia. The beneficial effect of aspirin has been found to be similar in subgroups according to different maternal characteristics, except for the presence of chronic hypertension, where no beneficial effect is evident. In addition, the effect size of aspirin has been found to be more pronounced in women with good compliance to treatment. In general, randomized trials are underpowered to investigate the treatment effect of aspirin on the rates of other placental-associated adverse outcomes such as fetal growth restriction and stillbirth. This article summarizes the evidence around aspirin for the prevention of preeclampsia and its complications.